On Sharpening of a Theorem of Ankeny and Rivlin (Analysis in Theory and Applications, 2020)
Let $p(z)=\sum^n_{v=0}a_vz^v$ be a polynomial of degree $n$, $M(p,R)=:\underset{|z|=R≥ 0}{\max}|p(z)|$ and $M(p,1)=:||p||$.Then according to a well-known result of Ankeny and Rivlin [1], we have for $R≥ 1$, $$M(p,R)≤ (\frac{R^n+1}{2})||p||.$$This inequality has been sharpened by Govil [4], who proved that for $R≥ 1$, $$M(p,R)≤ (\frac{R^n+1}{2})||p||-\frac{n}{2}(\frac{||p||^2-4|a_n|^2}{||p||})\left\{\frac{(R-1||p||)}{||p||+2|a_n|}-ln(1+\frac{(R-1)||p||}{||p||+2|a_n|})\right\}.$$In this paper, we sharpen the above inequality of Govil [4], which in turn sharpens theinequality of Ankeny and Rivlin [1].